2022
DOI: 10.52312/jdrs.2022.652
|View full text |Cite
|
Sign up to set email alerts
|

Severe spaghetti wrist injury: Should we expand the terminology from wrist to proximal forearm?

Abstract: Objectives This study aims to point out the key principles for the management of multicomponent soft tissue injuries of the wrist and forearm to discuss whether we should expand the term “spaghetti” from the wrist to forearm in such terrifying cases. Patients and methods Data from a total of 50 patients (44 males, 6 females; mean age: 48.5±25.7 years; range, 10 to 70 years) who were treated for multicomponent soft tissue injuries of the wrist and forearm, including at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Also, in studies investigating flexor tendon injuries in more proximal regions in the past, it has been reported that the size of the injury and accompanying vascular nerve injuries adversely affect clinical outcomes. [ 15 ] On the other hand, there are studies reporting that there is no significant relationship between digital nerve injury and flexor tendon repair outcomes. [ 7 , 16 , 17 ] In these studies, digital nerve injury did not affect the TAM value in patients with flexor tendon repair, but this does not indicate that digital nerve repair is not required in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in studies investigating flexor tendon injuries in more proximal regions in the past, it has been reported that the size of the injury and accompanying vascular nerve injuries adversely affect clinical outcomes. [ 15 ] On the other hand, there are studies reporting that there is no significant relationship between digital nerve injury and flexor tendon repair outcomes. [ 7 , 16 , 17 ] In these studies, digital nerve injury did not affect the TAM value in patients with flexor tendon repair, but this does not indicate that digital nerve repair is not required in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 , 7 ] However, it has been shown that, although the cure rate of distal radius fractures treated by internal fixation is high, some patients still have poor prognosis and functional recovery, which poses threats to their daily life and work. [ 8 ] Therefore, it is essential to predict the prognosis of such patients at the early stage. Fracture-related cytokines have often been used to predict the prognosis and recovery of patients in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Although improvements in tendon repair techniques and postoperative rehabilitation programs have reduced adhesion rates in tendon surgery, a significant adhesion rate still continues. [ 1 , 2 ]…”
Section: Introductionmentioning
confidence: 99%